2007
DOI: 10.1143/jjap.46.l483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Residual Impurities on Annealing Properties of Vacancies in Electroplated Cu Studied Using Monoenergetic Positron Beams

Abstract: Positron annihilation was used to probe vacancies in Cu films deposited by Ta/SiO2/Si using electroplating and sputtering techniques. During room temperature grain growth (i.e., self-annealing) of the Cu films, two different types of vacancies (small vacancy clusters such as divacancies and large vacancy agglomerates) were introduced into grains; the formation of such defects was enhanced by residual impurities. For electroplated Cu, isochronal annealing experiments revealed further agglomeration of vacancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This value is slightly smaller than the k value at the same temperature in this work (1.2×10 −16 m 2 /s). The more rapid Ni 3 Sn 4 growth for the electroplated Ni/Sn couples in this work may be due to the more defects (e.g., vacancies and grain boundaries) in the electroplated components [12,[22][23], which should enhance the diffusion of Sn and Ni.…”
Section: Reaction Kineticsmentioning
confidence: 87%
“…This value is slightly smaller than the k value at the same temperature in this work (1.2×10 −16 m 2 /s). The more rapid Ni 3 Sn 4 growth for the electroplated Ni/Sn couples in this work may be due to the more defects (e.g., vacancies and grain boundaries) in the electroplated components [12,[22][23], which should enhance the diffusion of Sn and Ni.…”
Section: Reaction Kineticsmentioning
confidence: 87%
“…The other method of void formation is the Kirkendall voids, which is observed at the Cu 3 Sn layer. This voiding could be related to the Kirkendall effect, which was attributed to the unequal diffusion rates of Cu and Sn in the IMC [29] and impurity segregation [30][31][32][33][34]. It is generally believed that Cu is the dominant diffusing species in Cu 3 Sn, a larger diffusion flux of Cu would occur from the Cu substrate [35][36][37].…”
Section: Correlation Of Void Formation With Reactive Metal Layersmentioning
confidence: 99%
“…It is generally believed that Cu is the dominant diffusing species in Cu 3 Sn, a larger diffusion flux of Cu would occur from the Cu substrate [35][36][37]. If the vacancies, left by the diffusing-out of Cu atoms, cannot be occupied, they would gather to form new micro-voids with impurity [30][31][32][33][34]. Consequently, if the unequal diffusion rate between Cu and Sn exists, the voids would increase continuously.…”
Section: Correlation Of Void Formation With Reactive Metal Layersmentioning
confidence: 99%
“…The value of S for the annihilation of positrons trapped by vacancies is larger than that for positrons annihilated from the interstitial sites. Recent positron annihilation spectroscopy studies have suggested that ECD-Cu films have a larger amount of vacancy clusters than PVD-Cu films [2][3][4]. In this paper, we investigate lattice defects in a PVD-CuSb dilute alloy film compared to a PVD-pure-Cu film by measuring the Doppler broadening of the annihilation radiation using a slow positron beam.…”
Section: Introductionmentioning
confidence: 99%